(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Pomegranate seed oil is a valuable natural source of biologically active compounds and rare fatty acids. Its most distinctive feature is the high content of conjugated linolenic acid, which exhibits strong antioxidant, anti-inflammatory, and cytoprotective properties. Scientific evidence indicates that pomegranate seed oil improves lipid metabolism, supports cardiovascular system function, and protects cells from oxidative damage. Furthermore, this oil demonstrates immunomodulatory effects, inhibits the progression of tumor-related processes, and contributes to the maintenance of hormonal balance. This annotation summarizes the chemical composition, biological activity, and pharmacological significance of pomegranate seed oil based on reliable data from international scientific literature.